2017
DOI: 10.1088/1361-6463/aa9bc3
|View full text |Cite
|
Sign up to set email alerts
|

The absorber realized by 2D photonic crystals with plasma constituents

Abstract: Herein, a tunable metamaterial absorber was realized by using two-dimensional (2D) plasma photonic crystals (PPCs). A photonic band gap (PBG) can be obtained in the proposed 2D PPCs, which runs at frequencies from 1.7 to 1.93 GHz. The fabricated absorber is tunable and is composed of excited plasma tubes with 2D square lattices. The resonances originate from the all-dielectric resonances. The plasma frequency is also measured. The experimental results agree with the simulation results. The fabricated absorber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…When the gas discharge tube is excited by ballast, part of the mercury vapor will adhere to the wall of the tube and form a thin mercury layer, which will cause intense reflection and scattering of some EM waves in the tube, consuming part of the energy. For the above reasons, we consider that the simulation results are consistent with the measured results, consistent with the experimental results reported in previous literature [11]. The simulation data are obtained by using the finite number of plasma elements.…”
Section: Plasma Diagnosissupporting
confidence: 90%
See 1 more Smart Citation
“…When the gas discharge tube is excited by ballast, part of the mercury vapor will adhere to the wall of the tube and form a thin mercury layer, which will cause intense reflection and scattering of some EM waves in the tube, consuming part of the energy. For the above reasons, we consider that the simulation results are consistent with the measured results, consistent with the experimental results reported in previous literature [11]. The simulation data are obtained by using the finite number of plasma elements.…”
Section: Plasma Diagnosissupporting
confidence: 90%
“…Kikel and Li et al proposed the concept of plasma limiter, which can protect against intense EM pulse [7,8]. The research results of Wang et al confirmed that two-dimensional plasma photonic crystals produce significant photonic bands [1,2,9] and can control the propagation of EM waves; Zhang et al investigated the effect of specific parameters on the transmission and absorption properties of incident waves [10,11]; Zhang et al used graphene and nonlinear plasmons to tailor the transmission characteristics of EM waves [12,13]. However, there are two problems in the current research.…”
Section: Introductionmentioning
confidence: 99%
“…Since the concept of PPCs was proposed, its transmission characteristics have been the focus of research. Sakai et al first proposed the concept of PPCs, constructed a helium discharge plasma array at atmospheric pressure, and investigated the bandgap of PPCs by experimental tests and numerical calculations [1,2]; Fan [3] and Wang et al [4], used dielectric barrier discharge (DBD) with two water electrodes to obtain a two-dimensional PPC with tunable lattice arrangement and photonic bandgap; Wang et al [5] designed a threedimensional woodpile type PPC and calculated and tested its transmission characteristics; Zhang [6], Wen [7], and Wang [8] composed a PPC using plasma discharge tubes and tested and calculated its transmission and absorption characteristics; V. I. Arkhipenko et al [9] 2 of 13 obtained PPCs using neon glow discharge arrays, placed them in waveguides, and studied the transmission characteristics of PPCs at X-band; V. S. Babitski [10] obtained a PPC using argon pulse discharge at atmospheric pressure and also calculated and tested the transmission characteristics of PPCs. The results show that the properties of PPCs are similar to those of metallic photonic crystals at high electron density.…”
Section: Introductionmentioning
confidence: 99%
“…In [11], Devarapu et al, utilized compact PC structures constructed from strongly absorbing media and achieved more than 92% absorption. Very recently, Wen et al [12] proposed a tunable metamaterial absorber by using 2D plasma PCs with excellent absorption of up to 84.3%. Moreover, preparing hybrid structures with PCs can also lead to the enhancement of absorption because the optical properties of these hybrids can radically differ from those of the individual elements.…”
Section: Introductionmentioning
confidence: 99%